(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
Tea is a popular beverage made from the leaves of evergreen shrub or tree Camellia sinensis, under the family Theaceae. Tea plant is subjected to the attack of insects, mites, nematodes and some plant pathogenic diseases. Tea production is greatly hindered due to these maladies. About 10-15% crop loss occurred by these pests per annum. In severe cases, it would be 100%. To combat these problems different groups of pesticides have been used in the tea fields since 1960. As tea is a consumable commodity, the effect of residue of pesticides in made tea is harmful to human health. In this context, biopesticides are being considered as environmentally safe, selective, biodegradable, economical and renewable alternatives for use in IPM programmes. Biopesticides are natural plant products and may be grown by the planters with minimum cost and extracted by indigenous methods. Biopesticides are secondary metabolites, which include alkaloids, terpenoids, phenolics, and minor secondary chemicals. It is estimated that as many as 2121 plant species have been reported to posses pest control properties. Botanicals like neem, ghora-neem, mahogoni, karanja, adathoda, sweet flag, tobacco, derris, annona, smart weed, bar weed, datura, calotropis, bidens, lantana, chrysanthemum, artemisia, marigold, clerodendrum, wild sunflower and many others may be grown by planters with minimum expense and extracted by indigenous methods. These botanical materials can be used as an alternative to chemical pesticides. These botanical extracts will help in controlling major pests of tea such as Helopeltis, red spider mite, aphids, thrips, jassid, flushworm, termites, nematodes etc. The present note reviews the information of most widely available indigenous plants that may be used for the control of insect pests of tea as a component of IPM. DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13924 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 16-23, December, 2011